Horizontal transfer and finalization of a reliable detection method for the olive fruit fly endosymbiont, Candidatus Erwinia dacicola - Bigiotti, Gaia (BMC Biotechnol, 2019)
BACKGROUND: The olive fly, Bactrocera oleae, is the most important insect pest in olive production, causing economic damage to olive crops worldwide. In addition to extensive research on B. oleae control methods, scientists have devoted much effort in the last century to understanding olive fly endosymbiosis with a bacterium eventually identified as Candidatus Erwinia dacicola. This bacterium plays a relevant role in olive fly fitness. It is vertically transmitted, and it benefits both larvae and adults in wild populations; however, the endosymbiont is not present in lab colonies, probably due to the antibiotics and preservatives required for the preparation of artificial diets. Endosymbiont transfer from wild B. oleae populations to laboratory-reared ones allows olive fly mass-rearing, thus producing more competitive flies for future Sterile Insect Technique (SIT) applications. RESULTS: We tested the hypothesis that Ca. E. dacicola might be transmitted from wild, naturally symbiotic adults to laboratory-reared flies. Several trials have been performed with different contamination sources of Ca. E. dacicola, such as ripe olives and gelled water contaminated by wild flies, wax domes containing eggs laid by wild females, cages dirtied by faeces dropped by wild flies and matings between lab and wild adults. PCR-DGGE, performed with the primer set 63F-GC/518R, demonstrated that the transfer of the endosymbiont from wild flies to lab-reared ones occurred only in the case of cohabitation. CONCLUSIONS: Cohabitation of symbiotic wild flies and non-symbiotic lab flies allows the transfer of Ca. E. dacicola through adults. Moreover, PCR-DGGE performed with the primer set 63F-GC/518R was shown to be a consistent method for screening Ca. E. dacicola, also showing the potential to distinguish between the two haplotypes (htA and htB). This study represents the first successful attempt at horizontal transfer of Ca. E. dacicola and the first step in acquiring a better understanding of the endosymbiont physiology and its relationship with the olive fly. Our research also represents a starting point for the development of a laboratory symbiotic olive fly colony, improving perspectives for future applications of the Sterile Insect Technique.